Minimally Invasive Approach for Resection of Masseteric Vascular Malformations. Issue 6 (September 2018) - Schultz, Benjamin D.; Gray, Rachel; Knobel, Denis; Tanna, Neil; Setabutr, Dhave; Cheng, Jeffrey A.; Ortiz, Rafael; Bastidas, Nicholas
Abstract : Objective: Vascular malformations (VMs) in the head and neck region often cause esthetic as well as functional problems for patients. Intramuscular VMs (IVM), such as those in the masseter, can cause severe facial asymmetry and typically are excised transcutaneously to facilitate wide exposure and safe dissection from the facial nerve. This requires extensive dissection, prolonged healing, and can lead to suboptimal facial scarring. Methods: We describe the technique of resecting large IVMs of the masseter muscle in 3 patients using an entirely intraoral approach with continuous nerve monitoring and without visible facial scarring or secondary deformity. Preoperative injection of sclerotherapy was performed to reduce intra-operative bleeding and optimize resection. Results: Successful excision was performed without complication in 3 patients to date. Total average operating room time was 120 minutes (range 95–145 minutes). Estimated blood loss was 213 mL (range 180–240 mL). The patients were discharged home either post-operative day (POD) 1 or 2, with 1 returning to work POD 4. Facial nerve function was normal postoperatively and no hematomas developed. Subjective masticatory function was equivalent to preoperative levels in all patients. Conclusions: Intraoral excision of VMs of the masseter muscle can be safely performed without added risk or complication. Continuous facial nerve monitoring allows minimally invasive approaches to be considered with less risk of iatrogenic facial nerve injury. We purport that this is a safe and effective method with substantially better esthetic outcomes compared with traditional transcutaneous approaches.